Firms in Ethiopia’s Industrial Parks : COVID-19 Impacts, Challenges, and Government Response - Mengistu, Andualem; Krishnan, Pramila; Maaskant, Koen; Meyer, Christian Johannes; Krkoska, Eduard (World Bank, Washington, DC, 2020)
The Coronavirus 2019 (COVID-19) pandemic poses a challenge for Ethiopia’s ambitious industrialization agenda focused on export-oriented light manufacturing. This note summarizes results from a survey of firms in Ethiopia’s industrial parks. The data suggests that over the past months, the pandemic has severely impacted firms’ ability to produce and sell their output. The availability and affordability of foreign inputs and the availability of labor are widely reported as constraints to production. Government support measures have not reached the majority of firms. After these initial demand- and supply-side shocks, firms in industrial parks are now entering a new uncertain phase: over the next six months, firms expect that orders will decrease by an average of 20 percent and employment by 17 percent compared to the same period last year. These findings illustrate the need for sustained support to protect firms and workers from the impacts of the pandemic and to preserve the significant investments made in this sector. Wage subsidy schemes and working capital loan programs will be appropriate to mitigate large-scale job losses.